2021
DOI: 10.1039/d0en01278e
|View full text |Cite
|
Sign up to set email alerts
|

Silicon dioxide nanoparticles orchestrate carbon and nitrogen metabolism in pea seedlings to cope with broomrape infection

Abstract: Phelipanche aegyptiaca is one of the most devastating agricultural weed pests as it poses a serious threat to crop production. Although few studies addressed the potentiality of silicon nanoparticles (SiNPs)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…For instance, a reduction in starch level and an elevation of sucrose metabolizing enzymes was observed. It is well known that soluble sugars such as glucose and sucrose are the most pivotal structural and energetic organic compounds in higher plants ( Shabbaj et al, 2021b ). Besides being osmoregulators, sugars possess obvious ROS scavenging properties ( Van den Ende, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a reduction in starch level and an elevation of sucrose metabolizing enzymes was observed. It is well known that soluble sugars such as glucose and sucrose are the most pivotal structural and energetic organic compounds in higher plants ( Shabbaj et al, 2021b ). Besides being osmoregulators, sugars possess obvious ROS scavenging properties ( Van den Ende, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of key enzymes involved in proline metabolism, i.e., pyrroline-5- carboxylate synthetase (P5CS), pyrroline-5-carboxylate reductase (P5CR), pyrroline-5-carboxylate dehydrogenase (P5CDH), proline dehydrogenase (ProDH), ornithine amino transferase (OAT), and arginase (Arg), were extracted [Tris-HCl buffer (50 mM, pH 7.4)] ( Shabbaj et al, 2021b ). The activities of OAT and ARG were assessed in KPO4 buffer (50 mM KPO4 buffer pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon (Si) is not essential for plants, but in drought stress, it can affect the water ratio in drought-affected plants, reduce stomatal conduction associated with protective cell turgor loss, improve the ability to extract water from the soil due to the promotion of root elongation and the regulation of aquaporin genes [12]. Si NPs can reduce oxidative stress by increasing antioxidant enzyme activities and decreasing reactive oxygen species (ROS) in plant leaf [7,[13][14][15]. In a salinity experiment with sweet peppers and different forms of Si, it was found that using SiO 2 NPs resulted in 15% higher plants, 34% higher fresh, and 36% dry biomasses and 11% higher total chlorophyll content and 30% yield compared to bulk Si [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Saleh et al [ 17 ] found that eCO 2 treatment enhanced the accumulation of phenolics, flavonoids, and tocopherols in wheat grown under NiO-NPs. Additionally, the role of CO 2 in regulating the C and N metabolism cannot be overlooked [ 62 ]. This could explain the accumulation of phenolics, tocopherols, and flavonoids in plants grown in a CO 2 -enriched atmosphere, where C and N intermediates and metabolic energy required for their biosynthesis are available [ 55 ].…”
Section: Discussionmentioning
confidence: 99%